Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/1541-4337.12808
|View full text |Cite
|
Sign up to set email alerts
|

Slow digestion‐oriented dietary strategy to sustain the secretion of GLP‐1 for improved glucose homeostasis

Abstract: Dysregulated glucose metabolism is associated with many chronic diseases such as obesity and type 2 diabetes mellitus (T2DM), and strategies to restore and maintain glucose homeostasis are essential to health. The incretin hormone of glucagon-like peptide-1 (GLP-1) is known to play a critical role in regulating glucose homeostasis and dietary nutrients are the primary stimuli to the release of intestinal GLP-1. However, the GLP-1 producing enteroendocrine L-cells are mainly distributed in the distal region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 244 publications
0
9
0
Order By: Relevance
“…Recently, growing evidence revealed that low glycaemic index (GI)/glycaemic load (GL) dietary patterns might be especially helpful for the management of diabetes (29). A slow digestionoriented dietary approach might be beneficial for improving glucose homeostasis (30). SDC is typically found in low GI/GL foods and induces a low glycemic response (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidence revealed that low glycaemic index (GI)/glycaemic load (GL) dietary patterns might be especially helpful for the management of diabetes (29). A slow digestionoriented dietary approach might be beneficial for improving glucose homeostasis (30). SDC is typically found in low GI/GL foods and induces a low glycemic response (31).…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella was positively correlated with mineral absorption ( Figure S4 ; Additional File 2: Supplementary Table S6 ). Minerals, carbohydrates, and proteins are food nutrients, and they are the main stimulators of glucagon-like peptide-1 (GLP-1), which over production can disrupt glucose homeostasis ( Qin et al., 2021 ). The lipopolysaccharide biosynthesis and lipopolysaccharide biosynthesis proteins pathways, which were significantly enriched in PDCs, are recognized pro-inflammatory factors that disrupt the intestinal barrier and cause metabolic disturbances ( Fabbiano et al., 2018 ); however, they are negatively correlated with bacteria enriched in PDCs and positively correlated with bacteria reduced in PDCs.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that Christensenella reduces oxidative stress in diabetes by regulating the levels of antioxidant enzymes and MDA. Generally, the ability of intestinal bacteria to improve diabetes works through the intestinal tract, where enteroendocrine L-cells secrete GLP-1, encoded by the proglucagon gene (GCG), stimulating insulin secretion and regulating glucose homeostasis ( Taşçı and Bingöl, 2018 ; Qin et al, 2021 ). The increased serum GLP-1 and GCG expression suggests that Christensenella intervention promotes GLP-1 secretion ( Figures 5D , G ).…”
Section: Discussionmentioning
confidence: 99%